Designing audio processing strategies to enhance cochlear implant users' music enjoyment - May, Lloyd; Hodges, Aaron; Park, So Yeon; Kaneshiro, Blair; Berger, Jonathan (Frontiers in Computer Science, 2024)
Cochlear implants (CIs) provide hundreds of thousands of users with increased access to sound, particularly speech, but experiences of music are more varied. Can greater engagement by CI users in the music mixing process mutually benefit them as well as audio engineers? This paper presents an exploratory mixed-methods study that leverages insights from CI users and professional audio engineers (AEs) in the investigation of techniques to enhance CI user music enjoyment and promote empathetic practices in AEs. Analysis of data collected over a multi-step process of surveys, interviews, and iterative cycles of sound mixing and feedback revealed two mixing strategies-namely essentializing and exaggeration of musical elements-common among mixes preferred by CI users. Participant responses also highlighted systemic ableism and audism in the music industry-an industry from which CI users report feeling excluded. Specifically, AEs felt inadequately trained around aural diversity considerations and experienced anxiety around their own aural diversity. In sum, this work contributes to insights into CI user music listening preferences; how AEs approach mixing for an aurally diverse audience; and discussion around the efficacy of CI simulation, user feedback, and AE peer feedback on mix enjoyment by CI users. Based on these findings, we offer several design insights that emphasize the need for customizable music listening tools centered around user agency and enjoyment.